Pengaruh Pengetahuan Dasar Desain terhadap Kreativitas Mendesain Busana Fase F DPB 2 di SMK Negeri 1 Jatirejo - Aisya Jasmine; Imami Arum Tri Rahayu (Journal on Education, 2024)
This research was held at SMK Negeri 1 Jatirejo. The type of research used is Expost facto. The research population of students in phase F class XI DPB 2 consisted of 31 students, with a saturated sampling technique. Data collection techniques use multiple choice tests, performance tests and questionnaires. The results of the collected data were processed using normality tests, linearity tests, heterogecidity tests, simple regression tests, and hypothesis tests. The results of the research show that basic knowledge of design reaches the very good category, and creativity in designing clothing reaches the good category, and the results state that basic knowledge of design has a positive influence on creativity in designing clothing with a magnitude of 93.9%, this value is supported by the t count and t table is 21,102>2,045 with a positive regression coefficient value. It was concluded that there was an influence of basic design knowledge on design creativity in phase F DPB 2 at SMK Negeri 1 Jatirejo.